PENGARUH INDEPENDENSI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA AUDITOR (Studi Pada Badan Pengawasan Keuangan Dan Pembangunan Daerah Provinsi Papua) - Siti Rofingatun (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2018)
This study aims to examine independence factor that affecting the style of leadership to the performance of auditor. This study was conducted at Finance and Regional Development Board of Papua Province. This study uses primary data, namely by distributing questionnaires to respondents.Respondents in the study were auditors totaling 47 people. The analytical tool in this study uses Smart-PLS, which must Assessed the Outer Model and the Structural Model or the Inner Model. The results of this study show partially the leadership style and independence affect the auditor'sperformance with a significance value of 0,000 and 0,025 respectively